Comparative in vitro analysis of the biological potential of Usnea florida (L.) Weber ex F.H. Wigg., Usnea intermedia (A. Massal.) Jatta, and Usnea lapponica vain and quantification of usnic acid (Indian Journal of Traditional Knowledge (IJTK), 2024)
The present study focused on the antioxidant, cytotoxic, antimicrobial, and DNA-protective effects of Usnea lapponica, Usnea intermedia, and Usnea florida, which are distributed in Turkey. The methanol extracts of these three lichen species were subjected to high-performance liquid chromatography (HPLC) analysis to quantify the amount of usnic acid and the highest amount was found in U. lapponica (3345.9±92.18 mg/gextract). Furthermore, the total phenolic and flavonoid contents were analyzed. Antioxidant capacity was evaluated by different chemical assays, together with antimicrobial, cytotoxic, and DNA-protective properties.The results of the antioxidant assays showed that U. lapponica exhibited the highest DPPH radical scavenging activity, whereas the extract that scavenged ABTS radicals more potently was identified as U. intermedia. The disc diffusion method was used to investigate the antimicrobial activity, and the strongest effect was observed in U. intermedia methanol extract with a zone value of 13 mm on Micrococcus luteus. In cytotoxicity experiments, U. florida extract (250 μg/mL; 36.03% viability) exhibited a high antiproliferative effect on A549 cells and U. intermedia (62.5 µg/mL; 23.65% viability) on MDA-MB-231 cells. DNA-protective effects were investigated using pBR322 plasmid DNA, and all the studied species were found to have DNA-protective effects. These results suggest that Usnea species may be potential candidates for the development of new phytopharmaceuticals and functional ingredients.